The Tune of Christian Apocalyptic: Paul and John in Concert - Moses, Robert E. (Theology today, 2018)
This article puts John and Paul in conversation concerning two issues: believers' partaking of food sacrificed to idols and the question of who were the primary actors in Jesus' death. While many modern interpreters see discord between John's treatment of food offered to idols and Paul's, this article argues that both John and Paul were informed by an apocalyptic worldview that sees demonic forces behind idolatry. As such, they are in harmony in their arguments that all foods explicitly identified as idol food must be rejected by believers. Furthermore, both John and Paul share an apocalyptic worldview that saw demonic forces as the primary actors in Jesus' crucifixion.